12-talspigerne i medierne: Rammesætning og stereotypificering af højtpræsterende piger og kvinder i det danske uddannelsessystem [Straight-A girls in the media: The framing and stereotypification of high performance girls and women in the Danish system of education] - Hansen, Kenneth Reinecke; Blom, Jonas Nygaard (MedieKultur: Journal of media and communication research, 2017)
Over the last couple of decades, girls and women have generally outperformed boys and men in the educational system, and in the Danish media, high-achieving girls and women are often referred to as straight A girls (Danish: 12-talspiger). In this article, we conduct a corpus linguistic analysis of the frames constructed around the concept of straight A girls in Danish national newspapers (N = 215 articles). The analysis shows that straight A girls are framed as sick and conform in a societal culture dominated by performance pressure. Th e frames are primarily manifested in contrasting pairs where seemingly positive attributes are aff ected by or turned into negative assessments, and in highly generalizing and exorbitant accounts reflecting a stereotypical conception of the girls. Conversely, the under-achieving boys are framed as easy-going and festive, but concurrently, also more innovative and independent. The article gives a critical account of such stereotypes, which could have substantial consequences for society’s understanding and treatment of girls and women under education.